2012
DOI: 10.3233/wor-2012-1370
|View full text |Cite
|
Sign up to set email alerts
|

Supporting workers with mental health problems to retain employment: Users' experiences of a UK job retention project

Abstract: Objectives: To understand experiences and perspectives of job retention project users in relation to challenges faced and support received; to develop explanatory insight into effective interventions. Participants: Fourteen employed users of a United Kingdom job retention project, with a range of mental health problems. Methods: Semi-structured individual interviews which were collaboratively designed with service users. Data analysis involved deductive and inductive thematic analysis, constant comparative ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 56 publications
0
45
0
4
Order By: Relevance
“…Two mixed-methods studies were excluded because it was not possible to differentiate data obtained with qualitative and quantitative methods [ 41 , 42 ]; a third study was excluded because we could not clearly identify the views reported by PwCDs [ 43 ]. This led to a total of 24 publications included in our review [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The flow chart of the study selection process is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two mixed-methods studies were excluded because it was not possible to differentiate data obtained with qualitative and quantitative methods [ 41 , 42 ]; a third study was excluded because we could not clearly identify the views reported by PwCDs [ 43 ]. This led to a total of 24 publications included in our review [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The flow chart of the study selection process is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Participants in the included qualitative studies were most often persons suffering from mental disorders [ 44 , 45 , 46 , 48 , 50 , 52 , 56 , 59 , 60 , 61 , 62 , 63 , 67 ]. Three studies included persons with musculoskeletal disorders [ 47 , 51 , 55 ], two studies persons with cancer [ 49 , 66 ], two studies persons with mental and musculoskeletal disorders [ 53 , 64 ], and two studies a broad mix of persons with long-term conditions [ 54 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Realistic assessments to ensure necessary accommodations and a good job match may require disclosure of mental health issues [6,21,71]. However, many people confronting mental health problems are hesitant to discuss these issues at the workplace [72,73]. The concern of how much to disclose is an ongoing dilemma for the trainee in the work environment, and not resolved at the outset [74].…”
Section: Substantive Discussionmentioning
confidence: 99%